An Analysis of Donald Grantham's Baron Cimetière's Mambo and Baron Samedi's Sarabande (and Soft Shoe). - Jackson, Bonnie Rebecca (East Carolina University, 2010)
The present analysis summarizes and clarifies the compositional tools and techniques employed in Donald Grantham's Baron Cimetière's Mambo (2004) and Baron Samedi's Sarbande (and Soft Shoe) (2005) in the context of their dance styles and literary influence. The investigation will begin with a summary of the composer's life and compositional training, followed by a review of literature on the aforementioned dance forms and the Haitian Voodoo loas, Baron Cimetière and Baron Samedi. The analysis is organized into two chapters and utilizes a number of post-tonal compositional theories.
Keywords: Music; Fine arts; Baron Cimetière's mambo; Baron Samedi's sarabande (and soft shoe); Grantham, Donald, 1947- . Baron Cimetière's mambo; Grantham, Donald, 1947- . Baron Samedi's sarabande (and soft shoe)